Anthocyanins reduce inflammation and improve glucose and lipid metabolism associated with inhibiting nuclear factor-kappaB activation and increasing PPAR-γ gene expression in metabolic syndrome subjects - Aboonabi, Anahita; Aboonabi, Arta (Free radical biology & medicine, 2020)
Anthocyanins exhibit antioxidant and anti-inflammatory activities via a multitude of biochemical mechanisms. However, the signaling pathways involved in the actions of anthocyanins against chronic inflammation are not fully understood. The effects of berry-rich anthocyanin supplements (320 mg/day) for four weeks were examined on features of metabolic syndrome components and the expression of PPAR-γ, Nrf2, and NF-κB dependent genes in MetS and healthy subjects. Total RNA was isolated from whole blood with the PAXgene proprietary blood collection system. Four weeks anthocyanin consumption significantly decreased fasting blood glucose (15.7% vs 3.2%), TG (18.2% vs -1.39%), cholesterol (33.5% vs 1.56%) and LDL (28.4% vs -15.6%) in the MetS compared to Control group (P-value < 0.05, 95% CI). There was a significant up regulation in the expression PPAR-γ gene associated with the lipid and glucose metabolism in MetS subjects which negatively correlated (P-value < 0.01) with the change in the FBG (r = -0.488), Cholesterol (r = -0.496), TG (r = -0.513) and LDL (r = -0.519). Moreover, anthocyanin supplementation decreases serum hs-CRP (-36.3% vs 6.25%) in MetS in compared to Control group (P-value < 0.05). Anthocyanin supplementation also down-regulated the expression of NF-κB dependent genes including TNF-α (-28% and -15%), IL-6 (-16.1% and -13.6%), IL-1A (-21.5% and -12.9%), PCAM-1 (-15% and -17.5%), and COX-2(-26% and -27%) in both MetS and Control group respectively (P-value < 0.05). The study results suggested that berry supplements improved selected features of metabolic syndrome and related cardiovascular risk factors. These benefits may be due to the inhibition of NF-κB dependent gene expression and enhancement of PPAR-γ. [Display omitted] •Anthocyanins improve FBG & lipid profile by up-regulating PPRAG mRNA.•Anthocyanins significantly decrease NF-kB dependent gene activation.•Anthocyanins inhibit TNF-α and COX-2 expressions and IL-6 production.•Anthocyanins improved selected features of cardiometabolic risk factors.